Reconstructing the late-Quaternary glacial history of northeastern Patagonia (43°S, 71°W): new insights from geomorphology, geochronology and numerical glacier modelling - Leger, Tancrède P. M. (The University of Edinburgh, 2022)
Former investigations conducting geomorphological mapping of Patagonia, a region formerly covered by an extensive ice sheet, have revealed a uniquely rich record of Quaternary glacial sediment-landform assemblages. Patagonia is located in the ocean-dominated southern mid-latitudes and in the pathway of major southern hemisphere circulation systems including the precipitation-bearing southern westerly winds, and the Antarctic circumpolar current. For these reasons, Quaternary glacier reconstructions from Patagonia can help identify the main drivers of climate and glacial events in the Southern Hemisphere. However, in northeastern Patagonia (39-46°S), geochronological data addressing the precise timing of Quaternary glacial events during Pleistocene glacial cycles are lacking. Indeed, in this region, little is known about the magnitude and timing of the Patagonian Ice Sheet’s response to climate events such as, for instance, the local Last Glacial Maximum (lLGM) and the last glacial termination. This Ph.D investigation attempted to fill in this knowledge gap, by producing a robust geochronological reconstruction that would describe the extent, stratigraphic relationship, characteristics and precise timing of most Quaternary glacial events preserved in a key valley system formerly host to major outlet glaciers of the northern Patagonian Ice Sheet. Firstly, this thesis presents the first detailed glacial geomorphological map of the Río Corcovado, Río Huemul and Lago Palena/General Vintter valleys (43°S; 71°W). This mapping effort enabled the identification of 25 distinct categories of sediment-landform assemblages related to the glaciogenic, glaciofluvial and glaciolacustrine activity of the former Patagonian Ice Sheet. This work revealed the preservation of at least eight distinct moraine-outwash complexes at the study site, each indicative of a former outlet-glacier advance/still-stand. Secondly, this thesis provides a new terrestrial cosmogenic nuclide exposure age (n = 38) chronology that establishes the precise timing of the local Last Glacial Maximum resurgences of the Patagonian Ice Sheet. In total, five distinct advances/still-stands of the Río Corcovado outlet glacier occurred over a 6-7 ka period, at 26.4 ± 1.4 ka, 22.4 ± 1.15 ka, 21.7 ± 0.9 ka, 20.7 ± 1.0 ka and 19.9 ± 1.1 ka. Additionally, this work reveals the onset of local deglaciation and the timing of final ice-sheet disintegration occurred at 20-19 ka and 16.3 ± 0.3 ka, respectively. Furthermore, evidences for the likely formation and drainage of three distinct glaciolacustrine phases at the study site were established. Dating revealed that the first phase occurred from 26.4 ± 1.4 ka, the second between ~21 and ~19 ka and the third between ~19 ka and ~16.3 ka. Thirdly, this thesis presents a separate reconstruction of an independent mountain-glacier advance dated to approximately ~18 ka using surface exposure dating. A series of numerical model simulations quantitatively reconstruct the geometry of this late-LGM glacier resurgence, and enable to estimate the local climate conditions at the time. This work for instance suggests that local precipitation must have been significantly higher than today during the late-LGM (~18 ka) glacial event, thus implying an equatorward migration of the Southern Westerly Winds at the time. Finally, this Ph.D. thesis features an additional terrestrial cosmogenic nuclide exposure-age chronology from the study site (n = 25) that focuses on dating the deposition of proglacial outwash plains and moraines formed during three extensive middle Pleistocene expansions of the Patagonian Ice Sheet. This dataset reveals, for the first time, that major glaciations occurred during the marine isotope stage eight and six intervals in northeastern Patagonia, while no prominent advances seem to have occurred during marine isotope stages four and three locally, in contrast with other Patagonian regions. This thesis’s findings enable us to draw hypotheses on the likely paleoclimate forcing mechanisms responsible for the timing of major middle-to-late Pleistocene glaciations at the southern mid-latitudes. This investigation also entails implications for better comprehending whether the former Patagonian Ice Sheet’s different sectors responded to major climate events synchronosuly or asynchronously during the late Quaternary.
Keywords: Patagonia; Quaternary period; Quaternary climate change; Patagonian glaciers; surface exposure dating